2018
DOI: 10.1007/s11295-018-1257-x
|View full text |Cite
|
Sign up to set email alerts
|

LTR retrotransposons from the Citrus x clementina genome: characterization and application

Abstract: Long terminal repeat retrotransposons (LTR-RTs) are a large portion of most plant genomes, and can be used as a powerful molecular marker system. The first citrus reference genome (Citrus x clementina) has been publicly available since 2011; however, previous studies in citrus have not utilized the whole genome for LTR-RT marker development. In this study, 3959 full-length LTR-RTs were identified in the C. x clementina genome using structure-based (LTR_FINDER) and homology-based (RepeatMasker) methods. LTR-RTs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 71 publications
1
15
0
Order By: Relevance
“…Many studies confirmed that the retrotransposons marker, e.g., ISTR had a superior discrimination capacity and have the flexibility to detect several polymorphic loci per individual reaction [60]. Recently, Du et al [61] suggested that retrotransposons (RT) occupied 28.1 Mb of the genome sequence, accounting for 9.74% of the entire genome. These results indicated that ISTR had an abundant presence of Ty-1 Copia retrotransposons, which permit obtaining useful polymorphism among the tested genotypes of Capparaceae and Cleome germplasm.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies confirmed that the retrotransposons marker, e.g., ISTR had a superior discrimination capacity and have the flexibility to detect several polymorphic loci per individual reaction [60]. Recently, Du et al [61] suggested that retrotransposons (RT) occupied 28.1 Mb of the genome sequence, accounting for 9.74% of the entire genome. These results indicated that ISTR had an abundant presence of Ty-1 Copia retrotransposons, which permit obtaining useful polymorphism among the tested genotypes of Capparaceae and Cleome germplasm.…”
Section: Discussionmentioning
confidence: 99%
“…LTR-RTs are extremely variable in size, ranging in plants from 4 kb to over 31–23 kb [39,40] (i.e., Ogre elements with >23 kb in length [41,42]) for functional and complete elements [12,42,43]. A key feature in this order is the presence of long terminal repeats (LTRs), which are two homologous (identical at the time of insertion) non-coding DNA sequences [44] located at both ends of the internal coding region and can range from a few hundred base pairs to more than 5 kb [26]. LTR-RTs contain one [45] or more open reading frames (ORF) [46] that are transcribed using host machinery [47] and code for gag and polyprotein ( pol ) genes.…”
Section: Structure Diversity Dynamics and Function Of Retrotranmentioning
confidence: 99%
“…This is seems caused by the distinction of the LTR-REMAP marker system. In subsequent studies, (Biswas et al, 2010a: Du et al, 2018 described that LTR-REMAP markers exhibited higher levels of heterozygosity due to the high copy number of effective alleles and its widespread distribution of LTR in citrus. The moderate value of the effective number of alleles per locus for SSR markers in comparison to LTR-REMAP may suggest the presence of many unique or less frequent alleles (Biswas et al, 2010a,b andAmar et al, 2011).…”
Section: Discriminating Capacity Of Ltr-remap and Ssr Markersmentioning
confidence: 99%
“…Many studies confirmed that the LTR-REMAP marker had a superior discrimination capacity and have ability to discover more polymorphic locus per individual reaction (Biswas et al, 2010b). Recently, (Du et al, 2018) recommended that LTR-RTs occupied 28.1 Mb of the genome sequence, accounting for 9.74% of the whole genome. These results suggested that LTR-REMAP had an abundant presence of Ty-1 copia retrotransposons, which allow obtaining advantageous polymorphism between the tested genotypes of citrus germplasm.…”
Section: Discriminating Capacity Of Ltr-remap and Ssr Markersmentioning
confidence: 99%
See 1 more Smart Citation